A Phase IIb, randomized, placebo‐controlled study of the SGLT2 inhibitor empagliflozin in patients with type 2 diabetes. Issue 8 (4th March 2013) - Ferrannini, E.; Seman, L.; Seewaldt‐Becker, E.; Hantel, S.; Pinnetti, S.; Woerle, H. J.
<x xml:space="preserve">Abstract</x> Aim This Phase IIb, randomized, double‐blind, placebo‐controlled trial evaluated the efficacy, safety, tolerability and pharmacokinetics of empagliflozin in patients with type 2 diabetes. Methods Four hundred and eight patients (treatment‐naïve or after a 4‐week wash‐out period) were randomized to receive empagliflozin 5, 10 or 25 mg once daily, placebo or open‐label metformin for 12 weeks. The primary endpoint was change in haemoglobin A1c (HbA1c) after 12 weeks. Results After 12 weeks' treatment, empagliflozin showed dose‐dependent reductions in HbA1c from baseline [5 mg: −0.4%, 10 mg: −0.5%, 25 mg: −0.6%; all doses p < 0.0001 vs. placebo (+0.09%)]. Fasting plasma glucose (FPG) decreased with empagliflozin [5 mg: −1.29 mmol/l, 10 mg: −1.61 mmol/l, 25 mg: −1.72 mmol/l; all doses p < 0.0001 vs. placebo (+0.04 mmol/l)]. Body weight decreased in all empagliflozin groups (all doses p < 0.001 vs. placebo). The incidence of adverse events (AEs) was similar in the placebo (32.9%) and empagliflozin (29.1%) groups. The most frequently reported AEs on empagliflozin were pollakiuria (3.3% vs. 0% for placebo), thirst (3.3% vs. 0% for placebo) and nasopharyngitis (2.0% vs. 1.2% for placebo). AEs consistent with urinary tract infections (UTIs) were reported in four (1.6%) patients on empagliflozin vs. one (1.2%) on placebo. Genital infections were reported in five (2%) patients on empagliflozin vs. 0% on placebo. No UTIs or genital infections led to premature discontinuation. Conclusions In patients with type 2 diabetes, empagliflozin resulted in dose‐dependent, clinically meaningful reductions in HbA1c and FPG, and reductions in body weight compared with placebo. Empagliflozin was well‐tolerated with a favourable safety profile.